Yield trial and sensory evaluation of sweetpotato cultivars in Highland Papua and West Papua Indonesia - Saraswati, P; Soplanit, A; Syaputra, A.T; Kossay, L; Muid, N; Ginting, E; Lyons, G (Journal of Tropical Agriculture, 2013)
With the aim of improving income and nutrition of indigenous highland people in Papua and West Papua provinces of Indonesia, trials involving introduced and local sweetpotato (Ipomoea batatas L.) cultivars were conducted in the Baliem Valley and Arfak Mountains (Minyambouw), Indonesia. Tuber yield and other agronomic traits, chemical content and sensory traits for 17 introduced and three local sweetpotato cultivars were evaluated. Total tuber yield varied from 7.4 to 20.8 Mg ha–1 in the Baliem Valley and from 1.9 to 14.4 Mg ha–1 in Minyambouw. The introduced cultivars produced higher yields than the local cultivars in both regions. Cultivar Papua Pattipi produced the highest yield in the Baliem Valley, while Sawentar produced the highest yield in Minyambouw. Cultivars varied in dry matter, protein, and betacarotene. Worembai was best for tuber flesh colour, taste, texture and sweetness in the Baliem Valley, while Helaleke and Papua Salosa scored highest for all sensory traits in Minyambouw. Introduced sweetpotato cultivars adapted well to both areas. In order to reduce malnutrition and increase income, it is important to grow several sweetpotato cultivars in each food garden, including high yielding cultivars and those with specific nutritional traits, such as high protein, provitamin A and anthocyanins. .